Human Capital, Entrepreneurial Capital and SMEs Performance of traditional herbal industries in Central Java, Indonesia: The Mediating Effect of Competitive Advantage - ., Ngatno; Apriatni, E.P.; ., Widayanto (Archives of Business Research, 2016)
This study provides new insights by examining effects of human capital and entrepreneurial capital on competitive advantage and performance. The samples of this study were owners of SMEs traditional herbal industries in Central Java, Indonesia. Thirty-five questionnaires were distributed, and they made 32 (91.43%) response rate. The data was analyzed using Generalized Structured Component Analysis (GSCA). The results reveal that: a) human capital and entrepreneurial capital have a positive effect on competitive advantage; b) human capital and entrepreneurial capital do not directly affect SMEs performance; c). Competitive Advantage fully mediates between human capital and entrepreneurial capital on SMEs performance. The findings offer an insight for the SMEs in traditional herbal industries: to increase their performance the human and entrepreneurial capital need to be developed. Limitations of this study, first, only small tradtional herbal industries were investigated. The small industries which are more specific in nature, such as the batik, toys, and craft SMEs, may result in different relations between the constructs of the models; second, the data was collected in a single central area of traditional herbal industry. There was no evidence of sampling bias, but future studies would benefit from inclusion of a wider geography scope; third the findings of this study also underscore the need for researchers to examine other factors which may also be antecedents of the SMEs performance and competitive advantage.